Composition and optical property controlled in In2O3/W2N nanostructure composites by nitrogen plasma assisted in-situ thermal annealing. (September 2017) - Saroni, Azianty; Alizadeh, Mahdi; Rahman, Saadah Abdul; Dee, Chang Fu; Goh, Boon Tong
Abstract: In2 O3 /W2 N nanostructure composites were grown by nitrogen plasma assisted in-situ thermal annealing at different hot-filament temperatures, T f . The in-situ thermal annealing changes the as-grown In2 O3 nanostructure to In2 O3 /W2 N nanostructure composite with decreasing the grain size from 200 to 300 nm to ~ 100 nm. The optical spectroscopy results indicate that the optical energy gap of the nanostructure composites (3.7–2.7 eV) can be effectively tailored by monotonically increasing the W2 N incorporation. The formation of W2 N is attributed to the high energetic ion bombardment of N adatoms and incorporation of W adatoms. Furthermore, the effects of the filament temperature, T f on the compositions in relation with the optical properties of the nanostructure composite are discussed.